Strategic Human Resource Development - Udom, Chanthana; Sachdev, Harin; Paiboonrattananon, Nongnooch; Juicharoen, Nhatphaphat (Business Administration and Management Journal Review, 2020)
Human is an important capital resource and strengthen to an organization. It affects to human resource development changing to be proactive. Human resource developer who adds value for an organization and important mechanism to human resource development activities. It is challenged to modify the capacity to the strategic partner for supporting strategic management in an organization. The purpose of this article is to present strategic human resource development concept as strategy formulation guideline in human resource to knowledge base in operating of human resource developer. It also supports the organization potential development responding to strategic, management knowledge and proficiency which lead an organization to target especially developing an organization for sustainable growth and high performance including with responding and achieving social holistic.